Integration Of Photogrammetry In Dental Education Curriculum: Potentials And Challenges - Budiono, Budiono; Failasufa, Hayyu (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Photogrammetry allows the creation of accurate 3D models of tooth structure and the oral cavity, offering improved anatomical visualization and a deeper understanding of complex structures in dentistry. This study aims to explore the integration of photogrammetry in the dental education curriculum, with a particular focus on the potential benefits and challenges facedMethod: Researchers used a qualitative approach with the main focus on scoping review. This technique makes a significant contribution to enhancing case-based learning and clinical skills development, by enriching students' practical and collaborative experiences.Result: Despite its enormous potential, the application of photogrammetry in dental education faces challenges, including the cost of hardware and software, as well as the need for comprehensive training for educators and students.Conclusion: This study recommends continued integration of photogrammetry in dental curricula, with a focus on developing resources and training to maximize its potential.